A hierarchically engineered polymer composite with a dual-scatter structure for enhanced passive radiative cooling - Park, Hyunho; Joo, Beom Soo; Kang, Gumin; Ko, Hyungduk; Kim, Jin Hong (Royal Society of Chemistry, 2025)
Passive daytime radiative cooling (PDRC) offers a sustainable cooling strategy by reflecting sunlight and emitting thermal radiation through the atmospheric window. However, conventional polymers used in PDRC composites often exhibit suboptimal optical properties due to detrimental chemical bonds like C？H and C[double bond, length as m-dash]O. Herein, theoretical and experimental comparative analyses are performed, demonstrating that an amorphous perfluoropolymer (CYTOP) composed solely of C？F and C？O？C bonds can enhance the cooling performance compared to conventional PDRC polymers. Leveraging the chemically near-ideal properties of CYTOP, a nanovoid-Al2O3 dual-scatter PDRC paint has been developed, achieving an outstanding solar reflectance of 98.2% and an infrared emittance of 96.4% at 80 μm thickness. This results in surface temperatures 5.4 °C below ambient and internal space temperatures in mini buildings, approximately 5 °C lower than those with commercial paints. This work offers strategic insights into materials and nanostructure design for efficient subambient radiative cooling applications.